The Implementation of the Policy on School Operational Assistance (BOS) at Junior High Schools in Indragiri Hilir Regency (A Case Study at Junior High Schools in Tembilahan Sub-District) - Yesrahmatulah Yesrahmatulah; Iqbal Miftakhul Mujtahid; Sofjan Arifin (Universitas Kristen Satya Wacana, 2021)
BOS policy is one of the public policies made by the government aiming at improving the quality of the human resources as the indicator of the progress of a nation’s development. This study aims to analyze and describe the implementation of BOS budget, and the supporting factors also inhibiting factors in implementing BOS at Junior High Schools in Tembilahan sub-district. The research design was qualitative using a descriptive method. The data and information were collected through an observation technique, interview, and documentation. Data analysis was conducted using classification steps, analysis, and data interpretation until the conclusion was drawn. The result showed that BOS policy was an appropriate and effective public policy for people in general and, particularly, for the school, teaching staff, and the students. The implementation of BOS at Public Junior High Schools in Tembilahan sub-district, was good and met the BOS technical guideline. However, it had still an obstacle that several school activities could not be accommodated using BOS budget. The supporting factors of the BOS policy implementation at Public Junior High Schools in Tembilahan sub-district such as a good communication between several relevant parties and the availability of competent human resources. Meanwhile, the inhibiting factors were financial resources and the characteristics of the policy were too rigid in the use in every school.